502 THE NUMBER OF LYMPHATIC CHANNELS DOES NOT AFFECT METASTASIS TO THE SENTINEL LYMPH NODE IN BREAST CANCER. (1st January 2006) - Tzou, D. T.; Tan, Y. -Y.; Hwang, J.; Florero, M.; Ewing, C.; Esserman, L.; Hwang, S.; Morita, E.; Leong, S. P.L.
Abstract : Introduction: The lymphatic channels are the routes by which cancer metastasizes. This study investigates whether a correlation exists between the number of channels and the likelihood of metastasis from the primary breast cancer site to the sentinel lymph node (SLN). Further, it examines the relationship of primary tumor characteristics with respect to these channels and SLN metastasis. Materials and Methods : : This study was a retrospective review of a large database of 695 patients with primary invasive breast carcinoma undergoing selective sentinel lymphadenectomy at a single institution from November 1997 to June 2005. Only patients with successful preoperative lymphoscintigraphy (with either channels or nodes identified) and pathology-determined SLN status were included. There were 532 patients that fit our study criteria. Results : : One hundred thirty-seven patients (24.8%) had one or more positive SLNs. A comparison of the percentages of positive SLN versus negative SLN for the different channel groups showed 0 channels, 25/137 (18.2%) with positive SLN vs 62/395 (15.7%) with negative SLN, p = .4865; 1 channel, 78/137 (56.9%) with positive SLN vs 244/395 (61.8%) with negative SLN, p = .3182; 2 or more channels, 34/137 (24.8%) with positive SLN vs 89/395 (22.5%) with negative SLN, p = .5845. No significant statistical relationship was found between the number of lymphatic channels and the frequency of SLN metastasis. The quadrant, type, and size of the tumor were also found to have no significant statistical relationship with the number of lymphatic channels. Metastasis was significantly associated with tumor size greater than 15 mm, poor tubular formation, and lymphovascular invasion. Conclusion: An increased number of lymphatic channels identified by preoperative lymphoscintigraphy does not appear to predict a higher likelihood of metastasis within the sentinel lymph node for all types of breast cancer. Metastasis to the sentinel lymph nodes is governed by the primary characteristics of the tumor rather than the number of lymphatic channels.